PENGEMBANGAN MEDIA CANVA MATERI LISTRIK STATIS - Evitamala Siregar; Rizki Fadilah (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
There is a lack of learning media in teaching physics material, one of which is static electricity, so students feel bored because what is taught is only theory and ordinary explanations. So the aim of this research is to develop media using Canva Design on static electricity material. Research and development methods (Research and Development) using the Borg and Gall model. This research has only reached the initial field trial stage due to time constraints. The instrument is a material expert validation sheet consisting of 10 statements that assess the appropriateness aspects of the material as well as linguistic aspects as well as the media expert's validity of 7 statements, namely appearance and technical aspects. The validity value using a Likert scale of 1 to 4 shows the value for the appropriateness aspect of the material is 87.5% and the linguistic aspect is 83.3%, the appearance aspect is 82.5% and the technical aspect is 96.97%.